2016
DOI: 10.21275/v5i5.nov163207
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Computer Vision Syndrome & Ergonomic Practices among Computer Engineering Students

Abstract: The aim of this study was to assess the frequency of CVS & related ergonomic practices among computer engineering students. A cross sectional study was conducted among computer engineering students of Superior University. A self-administrated questionnaire to assess computer vision syndrome and UC computer checklist was used. Simple randomized technique was used. A Sample of 170 computer engineering students was taken from a population of 1250 students of computer engineering department. All collected data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The advancement and wide adoption of Information Communication Technology (ICT) has made video display terminals (VDT) the standard working tools in offices [8–10]. These VDT gadgets have almost replaced traditional clerical works.…”
Section: Introductionmentioning
confidence: 99%
“…The advancement and wide adoption of Information Communication Technology (ICT) has made video display terminals (VDT) the standard working tools in offices [8–10]. These VDT gadgets have almost replaced traditional clerical works.…”
Section: Introductionmentioning
confidence: 99%
“…Others are problems relating to circadian rhythm seen in sleep disorders. [10][11] The pandemic has heightened the issues relating to CVS. Despite the harmful effects of CVS, the online learning goes on unhinged and has a strong promise to dominate the educational sector in the years to come.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study at Superior University, Pakistan in 2016 showed that the prevalence of CVS in engineering students was 72.4%. The results of the ergonomics analysis when using computers reported that most of the students did not apply the correct ergonomic principles (Hassan, Ehsan and Arshad, 2016). Eyestrain, eyes fatigue, dry and irritated eyes, slow eye focus, and headaches are the most common symptoms of CVS (Sari and Himayani, 2018).…”
Section: Introductionmentioning
confidence: 99%